Excystation and culturing of human and animal Giardia spp. by using gerbils and TYI-S-33 medium. - Wallis, P M (1986)
Mongolian gerbils were used as an animal model to excyst and host Giardia spp. isolated from meadow voles, dogs, beavers, and humans. Both cysts and trophozoites were used to establish infections. Gerbils were infected with Giardia duodenalis from beaver, dog, and human sources, and the trophozoites were extracted and cultured in Diamond TYI-S-33 medium. The use of gentamicin and ampicillin in the medium, coupled with treatment of gerbils with gentamicin before they were sacrificed, permitted the elimination of trophozoite purification techniques before culturing. An extract of whole bovine calf blood, CLEX, was substituted for fetal bovine serum in TYI-S-33 medium and was found to be both adequate and less expensive.